From a Botched Body without Organs to a Plastic Brain. A Reading of P.K. Dick’s "A Scanner Darkly" - Płomiński, Piotr (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2023)
This article analyzes the 1977 science-fiction novel A Scanner Darkly by Philip K. Dick, and focuses on the split personalities of the main character: Bob/Fred/Bruce. The reading is supplemented by the use of the concepts of Line of Flight and Body without Organs introduced by Gilles Deleuze and Félix Guattari in Capitalism and Schizophrenia as well as Catherine Malabou’s concept of brain plasticity. The article argues that the progressing deterioration of the protagonist’s mental state caused by drug abuse and social environment may be seen as a representation of a “botched BwO” – a body that has lost its productive potential and cannot be reintegrated into a stable territory. At the same time, I contend that the final chapter of the novel depicts a reparative transformation in which, thanks to brain plasticity, he is integrated into an autopoietic system of his environment.